The reconstruction of political economy : an introduction to post-Keynesian economics - Kregel, J. A. (London: Macmillan; [distributed in the U.S. by Halstead Press, New York, 1973)
The book presents the post- Keynesian theory in a form that will prepare the way for their study and further application.
With a foreword by Joan Robinson
Bibliography: p. [210]-213.
rpm 22/06/2017
Loans
Keywords: Keynesian economics; Neoclassical school of economics; Economics -- Theories -- 1945-1980; Economics $1 (BHistory $1 (B20th centurys